The impact of the elderly on inflation rates in developed countries - Vlandas, Timothee (London, 2016)
"What explains the cross-national variation in inflation rates in developed countries? Previous literature has emphasised the role of ideas and institutions, and to a lesser extent interest groups, while leaving the role of electoral politics comparatively unexplored. This paper seeks to redress this neglect by focusing on one case where electoral politics matters for inflation: the share of the population above 65 years old in a country. I argue that countries with a larger share of elderly have lower inflation because older people are both more inflation averse and politically powerful, forcing governments to pursue lower inflation. I test my argument in three steps. First, logistic regression analysis of survey data confirms older people are more inflation averse. Second, panel data regression analysis of party manifesto data reveals that European countries with more old people have more economically orthodox political parties. Third, time series cross-section regression analyses demonstrate that the share of the elderly is negatively correlated with inflation in both a sample of 21 advanced OECD economies and a larger sample of 175 countries. Ageing may therefore push governments to adopt a low inflation regime."